THE JURIDICAL ANALYSIS OF SUPERVISION IN THE DISTRIBUTION OF 3 KG LIQUEFIED PETROLEUM GAS (LPG) BASED ON REGULATION OF THE MINISTER OF ENERGY AND MINERAL RESOURCES OF THE REPUBLIC OF INDONESIA NUMBER 28 OF 2021 CONCERNING AMENDMENT TO REGULATION OF THE MI - Rheto Rizawan; Patricia E. Suryaningsih; Iskandar Iskandar (Universitas Bengkulu, 2023)
The conversion of kerosene to gas is a policy deemed appropriate by the government. This policy was taken to divert the use of kerosene fuel as a necessity for cooking because approximately in 2025 the kerosene in Indonesia is expected to run out, therefore the government is trying to find a substitute for kerosene, namely Liquefied Petroleum Gas (LPG). Moreover, Indonesian households continue to increase and the amount of kerosene has decreased and it is even difficult for the community to obtain it. In carrying out the policy of using LPG, the government has regulated the distribution of LPG. One of these regulations is the regulation of the Minister of Mineral Resources Number 28 of 2021 concerning amendments to the regulation of the Minister of Mineral Resources Number 26 of 2009 concerning the Supply and Distribution of Liquefied Petroleum Gas. The government has a role to control the process of distributing the 3 kg LPG to the public and the Ministry of Energy and Mineral Resources is responsible for supervising the supply and distribution of 3 kg LPG which involves related agencies such as the regional government. It is intended for the lower middle class elements. The distribution of 3 kg LPG under the government supervision aims to ensure that the 3 kg LPG is right on target, especially for the underprivileged and micro businesses. The supervision of the distribution of 3 kg LPG is very important to ensure smooth and affordable services and meet the needs of 3 kg LPG for the community. It is necessary to supervise and monitor the distribution of 3 kg LPG from distribution deviations, violations of the highest retail price (HET), scarcity and misuse of 3 kg LPG. Keywords: Supervision, Distribution, 3 Kg LPG